2016
DOI: 10.1126/science.aaf9621
|View full text |Cite
|
Sign up to set email alerts
|

A general catalytic β-C–H carbonylation of aliphatic amines to β-lactams

Abstract: Methods for the synthesis and functionalization of amines are intrinsically important to a variety of chemical applications. We present a general carbon-hydrogen bond activation process that combines readily available aliphatic amines and the feedstock gas carbon monoxide to form synthetically versatile value-added amide products. The operationally straightforward palladium-catalyzed process exploits a distinct reaction pathway, wherein a sterically hindered carboxylate ligand orchestrates an amine attack on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 54 publications
1
108
0
7
Order By: Relevance
“…Thus, the synthesis of aliphatic amines has always attracted considerable attention [1][2][3][4][5]. According to literature, the aliphatic amines were mainly produced through the reduction and ammonolysis processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis of aliphatic amines has always attracted considerable attention [1][2][3][4][5]. According to literature, the aliphatic amines were mainly produced through the reduction and ammonolysis processes.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Subsequent studies showed that even non-bulky secondary amines can be used as substrates to synthesize b-lactams if AdCO 2 Ha nd benzoquinone are used as additives. [42] Thep utative fourmembered palladacycle can also be intercepted by aryl boronic acids,t hereby resulting in net arylation of the C À H bonds. [43] Arylated product 85 can be accessed from amine 84.…”
Section: Amines (Free Amines)mentioning
confidence: 99%
“…Prompted by our interest in catalytic oxidative C–H carbonylation reactions, 1012 we reasoned that its merger with cobalt catalysis, guided by a pyridyl-derived auxiliary, would provide a distinct platform for C(sp 3 )–H activation using earth abundant metals. Herein, we report the development of an oxidative Co-catalysed carbonylative cyclisation procedure of aliphatic quinolinamides to yield a range of substituted succinimide products (Scheme 1C).…”
mentioning
confidence: 99%